PENINGKATAN KETERAMPILAN BERTANYA SISWA KELAS 2A SD MATERI PEDULI LINGKUNGAN BERBANTUAN MEDIA POP UP BOOK - Suaidah, Amida; Lilik Bintartik; Aldi Surya Kinasih; Alviena Tazky Amalia; Devi Restu Putpitasari; Hinggar Relung Puspita; Sinta Kiswoyo Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of questioning skills among lower-grade students in the Pancasila Education subject. The research aimed to improve the questioning skills of Grade IIA students at SDN Bareng 3, Malang City, regarding the topic of